1983
DOI: 10.1113/jphysiol.1983.sp014608
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of melatonin and thyroid hormones in the control of sleep, food intake and energy metabolism in the domestic fowl.

Abstract: SUMMARY1. Growing male domestic fowl of an egg-laying strain were fed ad libitum and injected intraperitoneally with melatonin or intramuscularly with triiodothyronine (T3) to study the effects on sleep, food intake, blood glucose, e.e.g., oxygen consumption and carbon dioxide production.2. Melatonin caused a dose-related depression of food intake with sleep and aphagia lasting for 21 hr following 8 mg, drowsiness and greatly reduced intake following 4 and 2 mg and a slight reduction in food intake after 1 mg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…It can be presumed that the high level of this hormone during the dark period is related to the decline in the metabolic rate occurring at this time. This conclusion is supported by the results of Bermudez et al (1983) who showed that injections of melatonin significantly decrease oxygen consumption in young cockerels. In the present experiment, we did not measure the plasma melatonin level in hens, but the literature data indicate that pinealectomy completely destroys the circadian rhythm of plasma melatonin levels (Pelham, 1975;Cogburn et al, 1987).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…It can be presumed that the high level of this hormone during the dark period is related to the decline in the metabolic rate occurring at this time. This conclusion is supported by the results of Bermudez et al (1983) who showed that injections of melatonin significantly decrease oxygen consumption in young cockerels. In the present experiment, we did not measure the plasma melatonin level in hens, but the literature data indicate that pinealectomy completely destroys the circadian rhythm of plasma melatonin levels (Pelham, 1975;Cogburn et al, 1987).…”
Section: Resultssupporting
confidence: 62%
“…This hypothesis is borne out by the results of Injidi and Fobres (1983) who found that pinealectomized cockerels fed during complete darkness, in contrast with control birds. On the other hand, melatonin injections reduce feed intake and cause sleep (Bermudez et al, 1983;Injidi and Fobres, 1983).…”
Section: Osmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Melatonin is produced rhythmically with high levels at night and low levels during the day in both diurnal and nocturnal species, 4 and its effect on food intake is often different (appetite stimulation, inhibition, or no effect) depending on the habits of each species. [10][11][12][13] In particular, our recent study on the central regulation of appetite in zebrafish demonstrated that melatonin is able to modulate not only food intake but also the most central appetite signals. 9 It has been demonstrated that melatonin, the hormonal mediator of biological rhythms, also acts at the peripheral level affecting adiposity, growth, and body weight, in both mammals and fish, although such effects are highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…MEL effects on food intake are controversial. It was demonstrated that MEL administration decreased the food intake in rats (Ishibashi et al, 1966), in domestic fowls (Bermudez et al, 1983), in hamsters (Bartness & Wade, 1985) and in fishes (Pinillos et al, 2001); while the other authors does not found any effect of MEL on food intake in rats (Dark et al, 1980;Wolden-Hanson et al, 2000). On the contrary, other studies in rodents reported the increase of food intake as a result of exogenous MEL administration (Bubenik & Pang, 1994;Shaji & Kulkarni, 1998) or melatonin agonist (Le Gouic et al, 1996).…”
Section: Introductionmentioning
confidence: 93%